Development of a native-locus dual reporter system for the efficient screening of the hyper-production of natural products in Streptomyces - Zhou, Jing-Yi; Ma, Bin-Bin; Zhao, Qing-Wei; Mao, Xu-Ming (Frontiers in Bioengineering and Biotechnology, 2023)
Streptomyces is renowned for its abundant production of bioactive secondary metabolites, but most of these natural products are produced in low yields. Traditional rational network refactoring is highly dependent on the comprehensive understanding of regulatory mechanisms and multiple manipulations of genome editing. Though random mutagenesis is fairly straight-forward, it lacks a general and effective strategy for high through-put screening of the desired strains. Here in an antibiotic daptomycin producer S. roseosporus, we developed a dual-reporter system at the native locus of daptomycin gene cluster. After elimination of three enzymes potentially producing pigments by genome editing, a gene idgS encoding the indigoidine synthetase and a kanamycin resistant gene neo were integrated before and after the nonribosomal peptidyl synthetase genes for daptomycin biosynthesis, respectively. After condition optimization of UV-induced mutagenesis, strains with hyper-resistance to kanamycin along with over-production of indigoidine were efficiently obtained after one round of mutagenesis and target screening based on the dual selection of the reporter system. Four mutant strains showed increased production of daptomycin from 1.4 to 6.4 folds, and significantly improved expression of the gene cluster. Our native-locus dual reporter system is efficient for targeting screening after random mutagenesis, and would be widely applicable for effective engineering of Streptomyces species with hyper-production of these invaluable natural products for pharmaceutical development.